Microcredit opportunities in developing and emerging economies: Lessons for how British banks can be more inclusive - Hubbard, Eleanor Hana (2017)
Despite the financial crisis taking place almost ten years ago, there still exists a problem of financial exclusion in the UK. The bottom of the Top of the Pyramid (ToP) market in the UK is an untapped opportunity for multinational banks. To address this, banks need to increase their understanding of the Base of The Pyramid (BoP) context, develop new approaches to overcome BoP obstacles, and create new commercially viable business models. The purpose of this study was to investigate whether lessons learned from the BoP microlending model could to help alleviate financial exclusion in the UK. The research examined The Grameen Foundation in Glasgow, looking at how the BoP group lending model has been adapted from Bangladesh to provide small business loans in the UK and the mechanisms of its workings in a developed country. This study contributes to the gap in the International Business literature; how emerging economy multinational enterprises (EMNES) create value through the process of reverse innovation, transferring knowledge from developing to developed economies. This case is particularly unusual because usually knowledge is transferred from developed to developing economies. The main findings from the exploratory case study demonstrated the paradox between maintaining the traditional Grameen microlending model, alongside adapting to the local cultural environment in Glasgow. The findings further emphasised the need for more accessible microfinance providers in the UK to provide small business loans to address the problem of financial exclusion.